Global Symposium on Millimeter-Waves (GSMM) 2015
DOI: 10.1109/gsmm.2015.7175440
|View full text |Cite
|
Sign up to set email alerts
|

Millimetre wave textile integrated waveguide beamforming antenna for radar applications

Abstract: In this work, a fully Textile Integrated Waveguide (TIW) beamforming antenna for its use in a radar system operating at 77 GHz is presented. The TIW beamforming antenna is based on a Substrate Integrated Waveguide (SIW) slot antenna array and it is designed to be manufactured completely with conductive and non-conductive threads using industrial textile machinery, avoiding subsequent sewing and adhesive processes for its integration in wearable or comformable systems. The antenna performs beam tilting from 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…A waveguide slot antenna made of a textile-filled waveguide is presented in [12], but the waveguide walls are made of copper foil, which is impractical for wearable applications. The application of surface-integrated waveguides (SIWs), adapted for textiles as textile-integrated waveguides (TIWs) [13][14][15][16][17], has also been proposed. A TIW comprises three layers: the top and bottom conductive layers are typically constructed from conductive fabric, while the central dielectric layer typically consists of traditional materials such as wool felt or polyester-based textile.…”
Section: Introductionmentioning
confidence: 99%
“…A waveguide slot antenna made of a textile-filled waveguide is presented in [12], but the waveguide walls are made of copper foil, which is impractical for wearable applications. The application of surface-integrated waveguides (SIWs), adapted for textiles as textile-integrated waveguides (TIWs) [13][14][15][16][17], has also been proposed. A TIW comprises three layers: the top and bottom conductive layers are typically constructed from conductive fabric, while the central dielectric layer typically consists of traditional materials such as wool felt or polyester-based textile.…”
Section: Introductionmentioning
confidence: 99%
“…Even though, the integration of the antenna into a single textile structure can contribute to an easier and faster industrial manufacturing process, and can also reduce the incurrences due to the hand-made manufacturing process. This concept was already presented in [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 In, 11 the research reported four beam SIW slotted antenna array with À20 -+20 beam scanning. The textile integrated waveguide (TIW) beamforming antenna is reported in, 12 90 twisted SIW multibeam antennas are presented in 13 where beam scanning is achieved through four 90 twisted SIW in which the two horizontal couplers fed vertical couplers. The frequency agile SIW slot antenna is presented in 14 to solve the problem of uniconductor SIW, which could not be used for electronically tunable applications, the top metallic layer consisting of a single slot.…”
Section: Introductionmentioning
confidence: 99%